Role of Clinical Pharmacist in Drug Therapy Management in a Teritary Care Hospital - Pokkuluri, Sri Sai Lakshmi Jayanthi; Srujana, Kode; Harsha, Bikkina Venkata Sai Sri; Chandana, Mavulati Sri; Ali, Shaik Faizan (Indian Journal of Pharmacy Practice)
Objectives: Drug Therapy Management is a collaborative approach between a physician and a pharmacist. Implementation of DTM in hospitals have a higher chance of reducing DRP’s and increase in patients’ Quality of Life. The aim of this study is to evaluate types, frequency, and ways for minimizing Drug Related Problems and identify the role of clinical pharmacist in Drug Therapy Management. Methods: A Prospective Observational study was carried out in a tertiary care teaching hospital in Bhimavaram. All the in-patients who satisfied the inclusion criteria were enrolled. Patient demographics and necessary clinical data was collected. MS Excel and Graphpad Prism 9 Software were used to analyze the data. Chi-Square Test was implemented to obtain significance between number of diseases, age, number of drugs prescribed, length of hospital stays with DRP’s. Results: Among 493 cases, total of 315 DRP’s were detected (mean = 2.58 DRP’s per patient). The highest occurring DRP was Drug Interactions (40.6%). Antibiotics (27.54%) were found to be highly contributing. The major cause for DRP’s was inappropriate combination of drugs or drugs and food (39.75%). Drug discontinuation (26.35%) was the most appropriate type of recommendation. Conclusion: Findings in this study signify the need of adaptation of Drug Therapy Management thereby improving healthcare system. Most of the medication errors can be prevented with the interventions of clinical pharmacist as they have broad knowledge of clinical pharmacokinetics, drug use and safety.
Keywords: Drug Therapy Management (DTM); Drug Related Problems (DRP); Clinical Pharmacist